Development and evaluation of a perfusion decellularization porcine heart model - Weymann, Alexander; Loganathan, Sivakkanan; Takahashi, Hiroaki; Schies, Carsten; Claus, Benjamin; Hirschberg, Kristóf; Soós, Pál; Korkmaz-İçöz, Sevil; Schmack, Bastian; Karck, Matthias; Szabó, Gábor (Circulation journal, 2011)
Background: Reports about the generation of 3-dimensional neoscaffolds for myocardial tissue engineering are limited. The architecture provided by perfusion decellularization of whole hearts would support the production of human-sized 3-dimensional living tissues from an acellular matrix. The aim of this study was to evaluate the potential of a perfusion decellularization model for whole heart tissue engineering. Methods and Results: Hearts were obtained from 12 German Landrace pigs from a selected abattoir. After preparation, the hearts were mounted and perfused on a modified Langendorff decellularization model specifically constructed for this reason. Decellularization was achieved by an ionic detergent-based perfusion protocol. The quality of the decellularization process was quantified by histology and fluorescence microscopy. Data regarding the presence of residual DNA within the decellularized hearts was measured with spectrophotometric quantification and compared to controls. After histological examination, all hearts lacked intracellular components but retained various types of collagen, proteoglycan and elastin. Quantitative DNA analysis demonstrated a significant reduction of DNA in decellularized hearts compared to controls (84.32±3.99ng DNA/mg tissue vs. 470.13±18.77ng DNA/mg tissue (P<0.05)). Conclusions: The modified Langendorff perfusion decellularization model described here is applicable for whole porcine hearts by removing cellular content and DNA. The resulting 3-dimensional matrix provides an interesting tool for further studies in the field of whole heart tissue engineering. (Circ J 2011; 75: 852-860)
Gesehen am 12.12.2022